The Kiriath-Jearim Archaeological Mission - Römer, Thomas (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Under the joint direction of Israël Finkelstein (Tel Aviv University), Christophe Nicolle (CNRS – Collège de France) and Thomas Römer (Collège de France), a new archaeological mission in Israel, at Deir el-Azar (the former Kiriath-Jearim or Kiriath-Baʿal) will start in the summer of 2017 from the 1st to the 31st of August. This mission (entitled The Vlad and Sana Shmunis Archeological Excavation at Bibilical Kiriath-Jearim) is a joint project of the University of Tel Aviv and the Collège de France.